High-Dimensional Immune Profiling by Mass Cytometry Revealed the Circulating Immune Cell Landscape in Patients With Intracranial Aneurysm - Ge, Peicong; Liu, Chenglong; Chan, Liujia; Pang, Yuheng; Li, Hao; Zhang, Qian; Ye, Xun; Wang, Jia; Wang, Rong; Zhang, Yan; Wang, Wenjing; Zhang, Dong; et al. (Frontiers in Immunology, 2022)
Background: Increasing evidence supports a critical role of chronic inflammation in intracranial aneurysm (IA). Understanding how the immunological alterations in IA provides opportunities for targeted treatment. However, there is a lack of comprehensive and detailed characterization of the changes in circulating immune cells in IA. Objective: To perform a comprehensive and detailed characterization of the changes in circulating immune cells in patients with IA. Methods: Peripheral blood mononuclear cell (PBMC) samples from IA patients (n = 26) and age-and sex-matched healthy controls (HCs, n = 20) were analyzed using high dimensional mass cytometry, and the frequency and phenotype of immune cell subtypes were assessed. Results: We identified 28 cell clusters and found that the immune signature of IA consists of cluster changes. IA patients exhibited dysfunction of immunity, with dysregulation of CD4+ T-cell clusters, increased B cells and monocytes, and decreased CD8+ T cells, DNT cells, and DPT cells. Moreover, compared with findings in HC, IA was associated with enhanced lymphocyte and monocyte immune activation, with a higher expression of HLA-DR, CXCR3, and CX3CR1. In addition, the expression of TLR4, p-STAT3, and the exhaustion marker PD1 was increased in T cells, B cells, and NK cells in IA patients. Conclusions: Our data provide an overview of the circulating immune cell landscape of IA patients, and reveal that the dysfunction of circulating immunity may play a potential role in the development of IA.